Biocontrol Potential of Aspergillus Species Producing Antimicrobial Metabolites - Ngo, Men Thi; Van Nguyen, Minh; Han, Jae Woo; Kim, Bomin; Kim, Yun Kyung; Park, Myung Soo; Kim, Hun; Choi, Gyung Ja (Frontiers in Microbiology, 2021)
Microbial metabolites have been recognized as an important source for the discovery of new antifungal agents because of their diverse chemical structures with novel modes of action. In the course of our screening for new antifungal agents from microbes, we found that culture filtrates of two fungal species Aspergillus candidus SFC20200425-M11 and Aspergillus montenegroi SFC20200425-M27 have the potentials to reduce the development of fungal plant diseases such as tomato late blight and wheat leaf rust. From these two Aspergillus spp., we isolated a total of seven active compounds, including two new compounds (4 and 6), and identified their chemical structures based on the NMR spectral analyses: sphaeropsidin A (1), (R)-formosusin A (2), (R)-variotin (3), candidusin (4), asperlin (5), montenegrol (6), and protulactone A (7). Based on the results of the in vitro bioassays of eleven plant pathogenic fungi and bacteria, sphaeropsidin A (1), (R)-formosusin A (2), (R)-variotin (3), and asperlin (5) exhibited a wide range of antimicrobial activity. Furthermore, when plants were treated with sphaeropsidin A (1) and (R)-formosusin A (2) at a concentration of 500 µg/mL, sphaeropsidin A (1) exhibited an efficacy disease control value of 96% and 90% compared to non-treated control against tomato late blight and wheat leaf rust, and (R)-formosusin A (2) strongly reduced the development of tomato gray mold by 82%. Asperlin (5) at a concentration of 500 µg/mL effectively controlled the development of tomato late blight and wheat leaf rust with a disease control value of 95%. Given that culture filtrates and active compounds derived from two Aspergillus spp. exhibited disease control efficacies, our results suggest that the Aspergillus-produced antifungal compounds could be useful for the development of new natural fungicides.